Local content requirements in the South African extractives sector: Do South Africa's local content requirements for the mineral and mining sector promote foreign direct investment? - Wheeler, Keanan Shane (Department of Private Law, 2022)
The South African Government has an interest in ensuring that South Africa derives benefit from the exploitation of its natural resources. In the South African mineral and mining industry, this interest extends to the proceeds acquired from participation therein. Participation in the mineral and mining industry, however, is high risk, capital intensive and often has long lead times from exploration to production. Due to these factors, exploiting South Africa's mineral resources with recourse to purely domestic financing, expertise and/or equipment is challenging, if not impossible. Therefore, the industry requires capital, investment, and input from foreign sources, namely by way of Foreign Direct Investment (FDI). To ensure that foreign participation in its mineral and mining industry allows for domestic benefit, and that said benefit is enhanced in accordance with its policy objectives, the South African Government has formulated and imposed Local Content Requirements (LCRs) for the industry. This dissertation analyses the question of whether the LCRs formulated and imposed in the South African mineral and mining industry promote the attraction of FDI. The argument made is that the overarching factor influencing the decision to invest in the South African mineral and mining industry is certainty. Pursuant thereto, this dissertation argues that, as presently formulated and implemented, the LCRs applicable to the South African mineral and mining industry do not ensure certainty and, accordingly, do not promote the attraction of FDI. In the light of this conclusion, this dissertation offers two recommendations to the South African Government to enhance certainty in respect of the LCRs applicable to the South African mineral and mining industry for the purpose of promoting the attraction of FDI.